Discounts as a Barrier to Entry - Ide, Enrique; Montero, Juan-Pablo; Figueroa, Nicolás (American Economic Review, 2016)
To what extent can an incumbent manufacturer use discount contracts to foreclose efficient entry? We show that off-list-price rebates that do not commit buyers to unconditional transfers—like the rebates in EU Commission v. Michelin II, for instance—cannot be anticompetitive. This is true even in the presence of cost uncertainty, scale economies, or intense downstream competition, all three market settings where exclusion has been shown to emerge with exclusive dealing contracts. The difference stems from the fact that, unlike exclusive dealing provisions, rebates do not contractually commit retailers to exclusivity when signing the contract. (JEL D43, D86, K21, L13, L14, L42, L60)